Solar energy utilisation for milk pasteurisation: A comprehensive review. (September 2018) - Panchal, Hitesh; Patel, Romil; Chaudhary, Sudhir; Patel, D.K.; Sathyamurthy, Ravishankar; Arunkumar, T.
Abstract: Due to use of fossil fuels for the human activities found a significant effect on the environment as well as people's health. Hence, the researchers from all around the world are searching for the sustainable solution through non-conventional sources of energy like wind, biomass, solar energy etc. Among all non-conventional sources of energy, solar energy is prevalent. Pasteurisation is a process of heating of food or liquid for the killing of bacteria. For pasteurisation of milk, dairy industries require boiler or heat exchanger, and it consumes energy, and sometimes they need fossil fuels. Hence, a primary aim of this review paper is to discuss various research works have conducted by researchers on milk pasteurisation system so an appropriate best solution can be found for sustainable development. Highlights: Discussed various research works have conducted by researchers on milk pasteurisation system. Application of flat plate collector and evacuated tubes used for solar milk pasteurisation system. Different solar milk pasteurization systems have reviewed and comparative analysis is presented.